Signal analysis and stochastic modeling of evoked responses in brain circuits grown in culture - Xue, Mengran; Taishi, Ping; Sahabandu, Dinuka; Roy, Sandip; Krueger, James (2017 IEEE Global Conference on Signal and Information Processing (GlobalSIP), 2017)
The evoked responses (i.e., input-output dynamics) of small brain circuits grown in isolation are studied, with a focus on understanding state changes related to sleep and waking. In particular, brain circuits grown on multi-electrode arrays are subject to impulse-train stimulations, and analyses are undertaken of the resulting electrical responses. The data analyses indicate that brain circuits fluctuate probabilistically between discrete states, which modulate spectral characteristics of the evoked response. Based on these observations, a stochastic switching model for evoked response profiles is proposed.